A ESCOLHA PELA MEDICINA DE FAMÍLIA ENTRE ESTUDANTES DE MEDICINA NO MUNDO TROPICAL: UMA REVISÃO DE LITERATURA CAREER CHOICE FOR FAMILY MEDICINE AMONG MEDICAL STUDENTS IN TROPICAL WORLD: A LITERATURE REVIEW - Afonso Henrique Teixeira Magalhães Issa; André de Castro Rocha; Isabella Camilo Daher; Bárbara Emily de Mello Heliodoro; Mariana Berquó Peleja; Marco Tulio Antônio Garcia-Zapata (UniEVANGÉLICA, 2017)
Introduction: Family Medicine is the essential speciality for strengthening primary health care in the world. Several surveys show the shortage of this expert in order to ensure universal coverage and sustainable health systems. Methodology: Literature review of researches conducted in the tropical regions of the world in the last 10 years that investigated factors influencing the choice of the Family Medicine (FM) among medical students. This study was designed following the International Protocol with Preferred Items for Systematic Literature Review Reports (PRISMA). Inclusion criteria were: original research (qualitative or quantitative), conducted among medical students, located between the tropics, including the choice of Family Medicine as a category for analysis. Results: Ten (10) researches were found that showed a less prestige of the FM than in temperate regions, low insertion of FM in medical curriculum in the tropics. We also found a limitation to conduct a comparative analysis on the low scientific production, the lack of validated and replicated methods and confusion of terms between generalists (without specialization) and specialized Family Doctors. Final Considerations: The research agenda that seeks to understand the factors influencing the choice for FM among medical students should be expanded, especially in tropical countries. Medical curriculum should be modified to contemplate more the FM as a medical specialty and public policies need to enhance the role of the professional in the health systems of these countries.